(untitled) (Journal of actual problems of jurisprudence, 2019)
In the article there is proved the approach according to which administrative legal proceedings can be viewed from the standpoint of judicial control over the legality of executive bodies’ administrative work. Proceedings concerning hearing and disposition of cases of administrative jurisdiction are defi ned as content of administrative procedure of judicial control over the legality. Administrative procedure of judicial control over the legality of administrative work of the executive power begins and ends with a legal fact that has a procedural implementation.